2004
DOI: 10.4018/jeco.2004100102
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Electronic Commerce in SMEs

Abstract: Partwell Limited is a small to medium sized (SME) manufacturing and supply company based in the United Kingdom. This case study discusses the circumstances that led the company to consider the implementation of two Internet Web sites for the purpose of conducting Electronic Commerce (e-commerce). The history and culture of Partwell are described, as are the histories and characteristics of key personnel involved in this e-commerce project. Furthermore, the company's previous experience with information and com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 0 publications
2
10
0
Order By: Relevance
“…This is supported by the findings that indicate that entirely 67% of respondents indicated that they embraced the adoption of e-commerce. The result is consistent with the finding of the study by Tucker & Lafferty (2004) and Ghobakhloo et al (2011).…”
Section: Multiple Regressionsupporting
confidence: 83%
“…This is supported by the findings that indicate that entirely 67% of respondents indicated that they embraced the adoption of e-commerce. The result is consistent with the finding of the study by Tucker & Lafferty (2004) and Ghobakhloo et al (2011).…”
Section: Multiple Regressionsupporting
confidence: 83%
“…A comparison of the ecommerce users with e-commerce nonusers indicates that the two groups were significantly different only in terms of size (t-value 2.93; p = .004, df = 148), not in terms of sector or number of years in business. The data therefore reflect the experiences of larger-than-overall-sampleaverage firms-something that might not be unexpected, given the greater constraints that small and medium enterprises have faced in adopting e-commerce (Tucker & Lafferty, 2004).…”
Section: Data Collection Extraction and Analysismentioning
confidence: 99%
“…The literature has also cited non-economic factors such as lack of business education, training or managerial experience [56,[66][67][68] as barriers to success for minority entrepreneurs.…”
Section: Barriers Facing Immigrant Entrepreneursmentioning
confidence: 99%